Implementasi Aplikasi Laporjalanku untuk Pemetaan dan Pelaporan Jalan Rusak di Wilayah Kota Tarakan - Wardani, Ade; Rosyda, Miftahurrahma (STMIK Palangkaraya, 2024)
Tarakan City has road facilities with various degrees of damage, ranging from minor to severe conditions. To address this issue, a WebGIS application is required to provide information about the road conditions. This research aims to develop the